SHAPING AMERICA'S PERCEPTION OF MUSLIMS: The Transnational Approach to Globalization’s Role in Popular Culture - Laliyo, Dyah Anastasia Fadhilah; Dewi, Karina Utami (Ulul Albab: Jurnal Studi Islam, 2024)
After the 9/11 tragedy in 2001, where terrorist attacks destroyed the WTC and the Pentagon, Muslims were widely represented as terrorists in American media. However, the representation of Muslims began to change from 2017 to 2022 in popular culture such as films and TV series. Instead of being depicted as terrorists or "bad guys," Muslims started to be portrayed more positively as "good guys" in some movies. It is worth questioning what factors or circumstances led to this change in the depiction of Muslims in American popular culture. Through a transnational approach, the authors find that the shift in perception of Muslim characters is a utilization of current popular culture trends, which emphasize diversity to meet American audience preferences, resulting in several globalization consequences. These consequences include the formation of a Muslim image adjusted to American standards, often conflicting with Islamic culture, and the homogenization of Muslim culture, which is often reduced or even omitted in Muslim characters in films. In short, the shift in perception of Muslim portrayals in American popular culture is based on three interrelated factors: capitalism, representation, and globalization.